Meningkatkan Aktivitas Belajar PKn Siswa Kelas IV Melalui Penerapan Strategi Firing Line - Suryanti, Suryanti (Science and Education Journal (SICEDU), 2022)
The purpose of this study was to increase student activity and learning outcomes in Civics subjects for Class IV students at SDN Blongsong II through the application of the firing line learning strategy. This type of research is Classroom Action Research. The research subjects were teachers and students of Class IV. Data collection techniques using observation techniques, tests, interviews, and documentation. The instruments used were observation sheets, test questions, and a list of grade IV students. The data analysis technique in this study uses an interactive analysis model consisting of three components, namely reduction, data presentation and verification. Prior to the implementation of the action, the level of student activity with the indicators: 1) actively working on questions 50.0%, 2) actively asking 33.3% questions, 3) Actively answering 41.7% questions, 4) actively submitting opinions 25.0%, 5) the activeness of making learning conclusions 33.3%. Minimum completeness criteria for Civics are 7.0. Student learning outcomes that have not been completed as much as 58.3%. While the students who have completed as many as 41.7%. The results showed an increase in each indicator, namely: 1). actively working on questions 100.0%, 2). actively asking questions 91.7%, 3). actively answer questions 100%, 4). activeness in filing opinions 91.7%, 5). activeness in making learning conclusions 83.3%. Learning activities affect student learning outcomes. The results showed that student learning outcomes increased by 58.3%, from 41.7% of students who completed the initial meeting to 100% in the second cycle. These results have reached the success indicator of 80%. It can be concluded that the application of the firing line learning strategy can increase the activity and learning outcomes of Class IV students at SDN Blongsong II.